Identification and expression profile analysis of chemosensory genes in pine needle gall midge, Thecodiplosis japonensis (Diptera: Cecidomyiidae) - Jiao, Jipeng; Zhu, Rui; Ren, Lili; Tao, Jing; Luo, Youqing (Frontiers in Physiology, 2023)
Insects have highly specialized and sensitive olfactory systems involving several chemosensory genes to locate their mates and hosts or escape from predators. Pine needle gall midge, Thecodiplosis japonensis (Diptera: Cecidomyiidae), has invaded China since 2016 and caused serious damage. Till now, there is no environmentally friendly measure to control this gall midge. Screening molecules with high affinity to target odorant-binding protein to develop highly efficient attractants is a potential pest management method. However, the chemosensory genes in T. japonensis are still unclear. We identified 67 chemosensory-related genes in the transcriptomes of antennae, including 26 OBPs, 2 CSPs, 17 ORs, 3 SNMPs, 6 GRs, and 13 IRs, using high throughput sequencing. Phylogenetic analysis of these six chemosensory gene families among Dipteran was performed to classify and predict the functions. The expression profiles of OBPs, CSPs and ORs were validated by quantitative real-time PCR. 16 of the 26 OBPs were biased expressed in antennae. TjapORco and TjapOR5 were highly expressed in the antenna of unmated male and female adults. The functions of related OBPs and ORs genes were also discussed. These results provide a basis for the functional research on chemosensory genes at the molecular level.